2003
DOI: 10.1080/00016350310002784
|View full text |Cite
|
Sign up to set email alerts
|

Subgingival microbiota levels and their associations with periodontal status at the sampled sites in an adult Sudanese population using miswak or toothbrush regularly

Abstract: Little information is available on the effect of miswak use on gingival microbiota. We assessed levels of 28 oral bacteria in subgingival plaque of adult Sudanese miswak (n = 38) and toothbrush users (n = 36) age range 20-53 years (mean 34.6 years) to study associations between these bacteria, oral hygiene method, and periodontal status at the sampled sites. A pooled subgingival plaque sample from 6 probing sites of 1 selected tooth in each jaw was obtained from each subject. Whole genomic DNA probes and the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
24
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 17 publications
2
24
0
1
Order By: Relevance
“…But there are inconsistent reports regarding herbal activities. These variation in the activity of herb results are comparable with other studies including Teka et al [32], Darout et al [22], Bakathir and Abbas [33], Togan et al [18], Khan et al [14]. Findings of these authors suggest that variation in results of herbs when applied against organism can come due to many reasons for example geographical location, harvesting conditions, chemical constituents and use of different techniques of extraction.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…But there are inconsistent reports regarding herbal activities. These variation in the activity of herb results are comparable with other studies including Teka et al [32], Darout et al [22], Bakathir and Abbas [33], Togan et al [18], Khan et al [14]. Findings of these authors suggest that variation in results of herbs when applied against organism can come due to many reasons for example geographical location, harvesting conditions, chemical constituents and use of different techniques of extraction.…”
Section: Discussionsupporting
confidence: 85%
“…Production of synthetic drugs effectively improves the health care facilities around the world. In developing countries still local herbal products are common to treat a lot of diseased conditions due to their cost effectiveness and less side effects [22]. Fabricant & Farnsworth in 2001 reported active compounds obtained from herbal products have 80% correlation between their traditional use and use in modern therapeutics [16, 23].…”
Section: Discussionmentioning
confidence: 99%
“…Using the checkerboard hybridization technique to compare subgingival plaque samples of regular miswak and toothbrush users, Darout et al (2003) reported significantly higher Aggregatibacter actinomycetemcomitans in the plaque of regular miswak users (Darout et al, 2003). In a clinical, controlled, cross-over study, Al-Otaibi et al (2004), using the same technique to compare subgingival plaque samples of miswak and toothbrush groups and reported significantly lower Aggregatibacter actinomycetemcomitans the miswak group (Al-Otaibi et al, 2004).…”
Section: Discussionmentioning
confidence: 94%
“…For these reasons, the World Health Organization recommends the use of chewing sticks as an effective tool for oral hygiene in areas where such use is customary (Sofrata et al, 2007). Thus, during recent years, many researchers throughout the world have studied miswak as a helpful plant in mouth and tooth hygiene and have demonstrated the antimicrobial, anti-caries and anti-periopathic properties of aqueous extracts of various chewing sticks (Gazi et al, 1990;Al-Lafi and Ababneh, 1995;Darout et al, 2003;Sarfaraz Khan et al, 2009;Sofrata et al, 2011).…”
Section: Introductionmentioning
confidence: 97%